(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Uremic pruritus is a common complication in patients with chronic kidney disease. While its cause is not known for certain, different treatments are currently applied. This study aimed to compare the effects of Avena sativa, diluted vinegar, and hydroxyzine on the reduction of uremic pruritus. Materials and Methods. In this crossover randomized clinical trial, 23 hemodialysis patients with uremic pruritus were randomly divided into 3 groups. The first group was treated with Avena sativa lotion, twice a day, for as long as 2 weeks; the second group received diluted vinegar; and the third group took hydroxyzine tablets for the same time span. After 3-day-long washout periods, the therapeutic methods were crossed over. The data were collected by a pruritus scale and a visual analogue scale, which were completed before and after the interventions. Results. Avena sativa lotion significantly decreased the mean scores of pruritus intensity, consequences, and the verbal descriptor, although it did not have a significant effect on the frequency of pruritus and the pruritic surface. Vinegar and hydroxyzine significantly decreased all of the scores. Conclusions. Avena sativa, vinegar, and hydroxyzine were effective in decreasing pruritus. Diluted vinegar and Avena sativa can be used as a complement to hydroxyzine, which is itself a common pharmaceutical therapy.